OPTIMISASI STRUKTUR STIFFENED PANEL PADA KULIT SAYAP PESAWAT âWHALEâ DENGAN KRITERIA LOCAL BUCKLING DAN GLOBAL BUCKLING - Ikhsan, Muhammad
Stiffened panel is an effective structure in resisting buckling loads. Its failure modes is quite complicated because there are so many dimensional parameters and different buckling modes. Some of them are the local buckling, flexural buckling, torsional buckling, inter-rivet buckling and wrinkling. Therefore, designing an efficient stiffened panel is a challenging problem. ESDU provides validated analysis tools that are commonly used by engineers and lecturer in aerospace engineering, process engineering and structural engineering fields. In this thesis we will optimize the stiffened panel structure under compression load with reference to ESDU 70003 and ESDU 71014. The structure that will be designed in this study is the upper wing skin structure near the wing-root of a 4 seaters amfibian aircraft. Multi-objective optimization is performed to determine the type of stiffener and the geometry of the stiffened panel which provide adequate buckling strength yet lightweight structure. Multi-objective optimization is performed by utilizing the tools provided in MATLAB software. Based on the result, it was found that in the selected case study the stiffened panel structure would be optimum with an Blade stringer integral cross-section with a total cross-sectional area of 2170 mm2, skin thickness of 2.27 mm, stiffener thickness of 3.55 mm, stiffener height of 19.94 mm, and stiffener spacing of 80 mm.